International Benchmarking of Teacher Training Programs: Lessons Learned from Diverse Education Systems - Asfahani Asfahani; Samar A. El-Farra; Khurshed Iqbal (CV. Edujavare, 2024)
Effective teacher training programs are critical to the quality of education systems worldwide. Comparison of teacher training programs between countries, known as international benchmarking, provides valuable insight into best practices and areas for improvement. This research aims to conduct an international benchmarking study to examine and compare teacher training programs in various educational systems. The research methodology chosen for this study was a Systematic Literature Review (SLR), which was used to understand the basic principles of Islamic education and their practical application in the Indonesian context. The data used in the SLR approach comes from scientific literature found in academic databases and other reliable sources of information. The analytical process in this research includes a thorough and systematic synthesis of related literature using a qualitative approach. The findings of this research reveal the diverse landscape of teacher training programs in various countries. Successful programs often emphasize practical classroom experience, ongoing professional development, and alignment with the specific needs of students and society. Challenges include limited resources, variations in program quality, and adaptation to rapidly evolving educational technologies and pedagogical approaches. This research underscores the importance of international benchmarking to inform and improve teacher training programs worldwide. Lessons from diverse education systems can guide policymakers, educators, and stakeholders in designing more effective and responsive teacher training initiatives. By promoting best practices and addressing common challenges, this research contributes to improving the overall quality of teacher education and, consequently, the quality of education itself in diverse global contexts.